2019
DOI: 10.22452/mjes.vol56no2.8
|View full text |Cite
|
Sign up to set email alerts
|

The Asymmetric Link between Public Debt and Private Investment in Malaysia

Abstract: This paper intends to examine the existence of asymmetric effect of public debt on private investment in Malaysia. As Malaysia's public debt has been rising in recent years the question has been raised on whether the persistently high debt level can negatively affect private investment or otherwise. This study, which uses non-linear autoregressive distributed lags (NARDL) estimation with data from 1980 to 2016, shows some evidence of asymmetrical effect in private investment-public debt nexus in both the long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
3
8
0
Order By: Relevance
“…who failed to accept the hypothesis of an inverted U-shaped relationship between public debt and economic growth in the developing economies. However, our results are consistent with the findings by Lau et al (2019), and Mabula and Mutasa (2019), who report similar results for Malaysia and Tanzania, respectively. 7…”
Section: Main Findingssupporting
confidence: 93%
See 2 more Smart Citations
“…who failed to accept the hypothesis of an inverted U-shaped relationship between public debt and economic growth in the developing economies. However, our results are consistent with the findings by Lau et al (2019), and Mabula and Mutasa (2019), who report similar results for Malaysia and Tanzania, respectively. 7…”
Section: Main Findingssupporting
confidence: 93%
“…In summary, we establish evidence for a nonlinear relationship between public debt and private investment for the emerging market economies, thereby lending credence to the findings by Lau et al (2019) and Mabula and Mutasa (2019), who report similar results for Malaysia and Tanzania, respectively. However, our finding is in contrast with that of Law et al (2021), who failed to accept the hypothesis of nonlinear relationship between the two variables, in the sample of developing economies they considered.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…When the theoretical and empirical literature on the subject is examined, it is seen that there is no definite judgment about the crowding-out and crowding-in effects. Some studies in the literature that have been found to cause the crowding out effect of public debt on private sector investments are as follows; Çaşkurlu (2020), Akram (2011), Lau et al (2019), Tülümce and Buyrukoğlu (2013), Altunöz (2013). Studies investigating the effect of public debt on public investments and found to cause the crowding out effect of empirical findings are as follows; Picarelli et al (2019), Heinemann (2006), Ncanywa-Masoga (2018), and Durkaya et al (2010).…”
Section: Extended Abstractmentioning
confidence: 99%
“…In addition, increasing private debt increases the demand for loans and raises the real interest rate, which discourages private investment. Traditionally, the interest rate channel is the main channel through which public debt impact capital formation (Lau et al, 2019). Increased public debt is expected to raise interest rates and distort allocation of capital in financial markets resulting in lower private capital formation in the crowding out channel.…”
Section: Introductionmentioning
confidence: 99%